The relationship between strategic leadership, organizational climate and quality management practices in Egypt public universities - Mohamed Aboudahr, Shorouk Mohamed Farag (2022)
Egypt’s Higher Education Vision was launched with a commitment to improving quality and sustainability in higher education. The quality management literature commonly cites the significance of leadership in higher education. However, the blending approach to quality management progress occurs at a slow pace in Egypt’s higher education and that requires a continuous effort of strategic leadership and a positive climate to implement quality management. Thus, this study aimed to identify the influence of strategic leadership (SL) and organizational climate (OC) on quality management practices (QMPs) in Egypt’s public university. In addition, the influence of organizational climate variable as mediator in the relationship between strategic leadership and quality improvement practices was also examined. The cross-sectional survey method was applied in the data collection process. A total of 429 respondents involving academic staff from Egypt’s public universities took part in this study. Quantitative data were analyzed using Statistical Package for Social Science (SPSS) and SMART PLS software. The study established the validity of the survey for the measures through confirmatory factor analysis. The findings of the study indicated that strategic leadership had no significant impact on quality management practices. However, organizational climate had a direct impact on quality management practices, and strategic leadership impacted organizational climate significantly. This study also revealed that organizational climate had a comprehensive mediating influence on the relationship between strategic leadership and quality management practices. In conclusion, this study provides a new understanding of the importance of organizational climate to quality management practices. The study also contributes theoretical insights on organizational climate as one mechanism in which strategic leadership may associate with quality management practices. In addition, this study could contribute to visionary practices to enhance strategic leadership thereby creating a climate and quality management practices in the context of Egypt higher education.